Infusion thrombophlebitis: the histological and clinical features. - Woodhouse, C. R. (Royal College of Surgeons of England, 1980)
Thrombophlebitis was induced in 8 greyhounds by intravenous infusion of naftidrofuryl (Praxilene), dextrose saline being used as a control. The histological features were the same in the treated and the control veins: circulating polymorphonuclear leucocytes became attached to and later infiltrated the vein endothelium. In more severe cases the deeper layers of the vein wall were affected. The clinical features in 97 patients receiving intravenous infusions of physiological saline, dextrose saline, 5% dextrose, or Hartman's solution are reviewed. Twenty-eight cases of thrombophlebitis were seen after an average of 54 h infusion; 22 presented with signs of inflammation and in 6 thrombosis occurred first. Thrombophlebitis occurs as a response to a number of different chemical and physical stimuli. The histological features are the same whatever the insult to the vein. It is an acute sterile inflammation without bacterial infection.